2012
DOI: 10.1159/000342080
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration Therapy for Cardiorenal Syndrome: Physiologic Basis and Contemporary Options

Abstract: Background: Heart failure (HF) has a high readmission rate in part due to conventional and recently developed therapeutic options having suboptimal results. Extracorporeal and peritoneal ultrafiltration have been advocated as more beneficial methods for fluid removal in decompensated or refractory HF, respectively. Methods: Traditional and emerging concepts explaining the pathophysiology of HF and the cardiorenal syndrome are reviewed. Extracorporeal and peritoneal ultrafiltration clinical trials are then disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Specifically, PD does not seem to activate the sympathetic nervous system, renin-angiotensin-aldosterone, endothelin, and vasopressin systems often seen after intravascular volume depletion seen with diuretics (19), and may even result in better preservation of residual renal function (20). There is also speculation that other harmful mediators may also be removed (including urate, atrial natriuretic peptide, tumor necrosis factor [TNF]-alpha, monocyte chemoattractant protein [MCP]-1 and interleukin 6 [IL-6], and a so-called myocardial depressant factor) (21).…”
Section: Benefits Of Pd Over Diureticsmentioning
confidence: 99%
“…Specifically, PD does not seem to activate the sympathetic nervous system, renin-angiotensin-aldosterone, endothelin, and vasopressin systems often seen after intravascular volume depletion seen with diuretics (19), and may even result in better preservation of residual renal function (20). There is also speculation that other harmful mediators may also be removed (including urate, atrial natriuretic peptide, tumor necrosis factor [TNF]-alpha, monocyte chemoattractant protein [MCP]-1 and interleukin 6 [IL-6], and a so-called myocardial depressant factor) (21).…”
Section: Benefits Of Pd Over Diureticsmentioning
confidence: 99%
“…Peritoneal ultrafiltration (UF) is a simple choice for daily fluid removal. Today, peritoneal dialysis (PD) is increasingly used to treat hypervolemic CHF patients who are resistant to conventional therapies, in particular when complicated by renal insufficiency (reviewed in [ 1 , 2 ]). It was demonstrated that PD improves the functional status, reduces hospitalization rate, and even may decrease mortality rate [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These mediators whose molecular weight ranges between 500 and 30000 Dalton can penetrate from the peritoneal membrane, by this way PD allows clearance of these agents while contributing to the support for the heart directly (46,47).…”
Section: Why Peritoneal Dialysis Is Chosen In the Treatment Of Heart mentioning
confidence: 99%